2015
DOI: 10.4238/2015.april.17.11
|View full text |Cite
|
Sign up to set email alerts
|

Case Report Whole-exome analysis of a child with polycystic kidney disease and ventriculomegaly

Abstract: ABSTRACT. Autosomal recessive polycystic kidney disease (ARPKD)is an inherited ciliopathy leading to progressive kidney and liver disease. Biallelic mutations in the PKHD1 gene underlie this condition. We describe a child with bilaterally enlarged cystic kidneys, portal hypertension, and cerebral ventriculomegaly. Molecular genetic investigations using whole-exome sequencing and confirmation using Sanger sequencing revealed a homozygous pathogenic mutation in PKHD1 underlying the clinical phenotype of ARPKD. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In the past years, some PKHD1 mutations were identified by exome sequencing. 23,30,31 Recently, Tavira et al 51 estimated that the cost of the NGS of the 30 samples, plus Sanger sequencing of PCR-fragments to assign the identified mutations, was ∼ 3.5-fold lower than the Sanger sequencing of all the PKHD1 amplicons on an ABI3130xl sequencer. Besides, Sanger sequencing-based molecular screening would have required several weeks, whereas the NGS project was completed in only 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, some PKHD1 mutations were identified by exome sequencing. 23,30,31 Recently, Tavira et al 51 estimated that the cost of the NGS of the 30 samples, plus Sanger sequencing of PCR-fragments to assign the identified mutations, was ∼ 3.5-fold lower than the Sanger sequencing of all the PKHD1 amplicons on an ABI3130xl sequencer. Besides, Sanger sequencing-based molecular screening would have required several weeks, whereas the NGS project was completed in only 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…familial Mediterranean fever (MEFV gene) [120], thiamine-responsive megaloblastic anemia (SLC19A2 gene) [121], cerebellar atrophy and developmental delay (PLA2G6, KIF1A and MOCS2A genes) [122], micro-/anophthalmia (VSX2, SOX2, and FOXE3 genes) [123], RAGdeficiency (RAG1 and RAG2 genes) [124], auriculocondylar syndrome (PLCB4, GNAI3, and EDN1 genes) [125], ectodermal dysplasia (EDA, EDAR, and EDARADD genes) [126], 3phosphoglycerate dehydrogenase deficiency (PHGDH gene) [127], carpenter syndrome (RAB23 gene) [128], disorders/differences of sex development (NR5A1, CYP19A1, AMH, AMHR2, WT1, HHAT, and FANCA and in the X-linked genes KDM6A and ARX genes) [129] and autosomal recessive polycystic kidney disease (PKHD1 gene) [130]. WES studies in Iraqi people revealed associated genes of epileptic encephalopathy (SLC13A5 gene) [131],…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…Studies (WES) in Egyptian individuals revealed associated genes of primary hyperoxaluria type I ( AGXT gene), infantile hypercalcemia/hypophosphatemia/nephrolithiasis ( SLC34A1 gene) [ 115 ], severe combined immunodeficiency ( JAK3 gene) [ 116 ], propionic acidemia ( PCCA gene) [ 117 ], sulfite oxidase deficiency ( SUOX gene), molybdenum cofactor deficiency ( MOCS2 gene) [ 118 ], primary hereditary microcephaly ( ASPM gene) [ 119 ], familial Mediterranean fever ( MEFV gene) [ 120 ], thiamine-responsive megaloblastic anemia ( SLC19A2 gene) [ 121 ], cerebellar atrophy and developmental delay ( PLA2G6 , KIF1A and MOCS2A genes) [ 122 ], micro-/anophthalmia ( VSX2 , SOX2 , and FOXE3 genes) [ 123 ], RAG-deficiency ( RAG1 and RAG2 genes) [ 124 ], auriculocondylar syndrome ( PLCB4 , GNAI3 , and EDN1 genes) [ 125 ], ectodermal dysplasia ( EDA , EDAR , and EDARADD genes) [ 126 ], 3-phosphoglycerate dehydrogenase deficiency ( PHGDH gene) [ 127 ], Carpenter syndrome ( RAB23 gene) [ 128 ], disorders/differences of sex development (NR5A1, CYP19A1, AMH, AMHR2, WT1, HHAT, and FANCA and in the X-linked genes KDM6A and ARX genes) [ 129 ] and autosomal recessive polycystic kidney disease ( PKHD1 gene) [ 130 ]. WES studies in Iraqi people revealed associated genes of epileptic encephalopathy ( SLC13A5 gene) [ 131 ], juvenile neuronal ceroid lipofuscinoses ( CLN3 gene) [ 132 ], inherited thrombocytopenia ( FYB gene) [ 133 ], microcephaly ( TMX2 gene) [ 134 ], non-syndromic retinal dystrophy ( POC1B gene) [ 135 ], progressive pseudorheumatoid dysplasia ( WISP3 gene) [ 136 ], dedicator of cytokinesis 8 deficiency ( DOCK8 gene) [ 137 ], and developmental delay ( MED27 gene) [ 138 ].…”
Section: Other Genetic Diseasesmentioning
confidence: 99%